Adsorption of Aqueous Using Granular Adsorbents from Accanthospermum hispendum DC - Gaya, Umar Ibrahim; Zubair, Sunusi A. (Journal of Science and Technology, 2021)
Granular activated carbons have been important adsorbents for the decontamination of aqueous environmental contaminants. Acanthospermum hispidum weed represents a ready available source of low-cost adsorbents in sub-Saharan Africa that has barely been paid attention. The effects of pH, contact time, concentration, adsorbent dosage, particle size and temperature on the adsorptive removal of Pb (II) from aqueous solutions over activated carbon granules from the thorns of Accanthospermum hispindum (AC-T) were for the first time investigated and compared with those of the leaves (L), the sodium hydroxide modified thorns (NaOH-T) and regular thorns (T) of this plant. These adsorbents were characterised by the surface charge analysis, scanning electron microscopy (SEM) and the Attenuated Total Reflectance Fourier Transform infrared (ATR FTIR) spectroscopy. The SEM revealed a wafer-like appearance for the AC-T with a large distribution of open pores. The adsorption data of lead uptake onto the adsorbents were examined using two pseudo-order kinetic schemes and three isotherm models. To fully understand the adsorption capacities of the adsorbents, batch desorption recoveries were studied. The FTIR depicted the various functionalities responsible for the adsorption. Adsorption over AC-T was found to agree with pseudo second-order kinetic scheme, the Langmuir and Freundlich isotherm. This material exhibited the highest adsorption capacity. The order of reusability of the adsorbents is T < AC-T < NaOH-T.